Evaluation of piperonyl butoxide in enhancing the efficacy of pyrethroid insecticides against resistant Anopheles gambiae s.l. in Ghana - Dadzie, S.K.; Chabi, J.; Asafu-Adjaye, A.; Owusu-Akrofi, O.; Baffoe-Wilmot, A.; Malm, K.; Bart-Plange, C.; Coleman, S.; Appawu, M.A.; Boakye, D.A. (Malaria Journal, 2017)
Background: Malaria vector control methods involving the use of pyrethroids remain the strategies being used against malaria vectors in Ghana. These methods include the use of long-lasting insecticidal nets and indoor residual spraying in many areas in Ghana. However, there is evidence that pyrethroid resistance is widespread in many areas in Ghana. Synergists have been shown to be useful in inhibiting the enzymes that are responsible for the development of resistance and hence enhance the insecticide susceptibility of Anopheles gambiae sensu lato (s.l.) in many areas. The present study investigated the effect of piperonyl butoxide (PBO) on the susceptibility status of An. gambiae s.l. across some sentinel sites in Ghana. Methods: Three to five day old An. gambiae s.l. reared from larvae were used in WHO susceptibility tube assays. Batches of 20-25 female adult An. gambiae s.l. were exposed simultaneously to the insecticide alone and to the PBO + insecticide. The knock down rate after 60 min and mortality at 24 h were recorded. Results: Deltamethrin and permethrin resistance of An. gambiae s.l. was observed in all the sites in 2015 and 2016. The mortality after 24 h post exposure for deltamethrin ranged from 16.3% in Weija to 82.3% in Kade, whereas that for permethrin ranged from 3.8% in Gomoa Obuasi to 91.3% in Prestea. A significant increase in susceptibility to deltamethrin and less to permethrin was observed during both 2015 and 2016 years in most of the sites when An. gambiae s.l. mosquitoes were pre-exposed to PBO. Conclusion: Findings from this study showed that the use of PBO significantly enhanced the susceptibility of An. gambiae s.l. mosquitoes in most of the sentinel sites. It is recommended that vector control strategies incorporating PBO as a synergist can be effective in killing mosquitoes in the presence of deltamethrin and permethrin resistance. © 2017 The Author(s).
Keywords: Anopheles gambiae; Insecticide resistance; Piperonyl butoxide; Pyrethroids